THE INFLUENCE OF DIGITAL MARKETING, USE OF ACCOUNTING INFORMATION AND SOCIAL SUPPORT FOR BUSINESS SUCCESS WITH SELF-EFFICACY AS A MODERATING VARIABLE - Liza Irhamna (UPT Publikasi Ilmiah UNISBA, 2025)
Abstract. Small and Medium Enterprises (SMEs) are one of the keys to the regional and national economy. The number of SMEs assisted by the Medan City government is 17.75% of the total SMEs registered in Medan City. This study aims to analyze the influence of marketing digitalization, the use of management accounting information, and social support on business success with self-efficacy as a moderating variable (a study of SMEs in Medan). This study is a quantitative study with an associative approach with a population of 450 SMEs that use Digital Marketing in their operational activities. The sample in this study was 82 SMEs assisted by the Medan City Government who use Digital Marketing in their operational activities. Primary data was obtained using a structured questionnaire with the aim of collecting information from SMEs in Medan that export products and are assisted by the Medan City government. Data management in this study uses SEM smartPLS software, with the results of the study being that digital marketing has an effect on business success, the use of management accounting information has an effect on business success, social support has an effect on business success, digital marketing has an effect on business success moderated by self-efficacy, the use of management accounting information has an effect on business success moderated by self-efficacy, and social support has a negative effect on business success moderated by self-efficacy.